French language students’ perception of online learning during post-COVID-19 - Wan Mokhtar, Wan Ikhlas; Bang Bang Ardiansjah, Mohd Redzuansyah (Gading Journal for Social Sciences, 2024)
Following the onset of the COVID-19 outbreak in Malaysia, the country initiated the relaxation of the Movement Control Order (MCO). Despite the reversion to face-to-face instruction, online learning, or e-learning, continues to be employed in all university institutions. Therefore, in response to this gap, this study focused on the perception of 30 French language students towards online learning post-COVID-19 at the Faculty of Modern Languages and Communication, Universiti Putra Malaysia (UPM). Data were collected using a 7-sections questionnaire. Descriptive analysis showed that the students preferred recorded class sessions, quizzes, or assignments. They perceived online classes as very structured and similar to face-to-face learning, with a consensus of 0.64. Students also felt that online learning can increase their self-discipline and responsibility. These findings suggest significant implications for the future of educational delivery, including the potential for enhanced student engagement and satisfaction through the integration of recorded sessions, structured breaks, and frequent assessments. This study concluded that the perception of French language students towards online classes post-pandemic is positive.